Lung cancers attributable to environmental tobacco smoke and air pollution in non-smokers in different European countries: A prospective study - Vineis, P; Hoek, G; Krzyzanowski, M; Vigna-Taglianti, F; Veglia, F; Airoldi, L; Overvad, K; Raaschou-Nielsen, O; Clavel-Chapelon, F; Linseisen, J; Boeing, H; Trichopoulou, A; et al. (2007)
Background. Several countries are discussing new legislation on the ban of smoking in public places, and on the acceptable levels of traffic-related air pollutants. It is therefore useful to estimate the burden of disease associated with indoor and outdoor air pollution. Methods. We have estimated exposure to Environmental Tobacco Smoke (ETS) and to air pollution in never smokers and ex-smokers in a large prospective study in 10 European countries (European Prospective Investigation into Cancer and Nutrition)(N = 520,000). We report estimates of the proportion of lung cancers attributable to ETS and air pollution in this population. Results. The proportion of lung cancers in never- and ex-smokers attributable to ETS was estimated as between 16 and 24%, mainly due to the contribution of work-related exposure. We have also estimated that 5-7% of lung cancers in European never smokers and ex-smokers are attributable to high levels of air pollution, as expressed by NO2 or proximity to heavy traffic roads. NO2 is the expression of a mixture of combustion (traffic-related) particles and gases, and is also related to power plants and waste incinerator emissions. Discussion. We have estimated risks of lung cancer attributable to ETS and traffic-related air pollution in a large prospective study in Europe. Information bias can be ruled out due to the prospective design, and we have thoroughly controlled for potential confounders, including restriction to never smokers and long-term ex-smokers. Concerning traffic-related air pollution, the thresholds for indicators of exposure we have used are rather strict, i.e. they correspond to the high levels of exposure that characterize mainly Southern European countries (levels of NO2 in Denmark and Sweden are closer to 10-20 ug/m3, whereas levels in Italy are around 30 or 40, or higher). Therefore, further reduction in exposure levels below 30 ug/m(3 )would correspond to additional lung cancer cases prevented, and our estimate of 5-7% is likely to be an underestimate. Overall, our prospective study draws attention to the need for strict legislation concerning the quality of air in Europe. © 2007 Vineis et al; licensee BioMed Central Ltd.